Os "sem religião" no ciberespaço: interfaces da religiosidade nas comunidades virtuais - Villasenor, Rafael Lopez (2013)
This thesis has as its object of study and research analyzing people with no religious belief in the cyberspace through the virtual communities, mainly within Orkut, for being the social network used by most Brazilians as a means of disseminating ideas and defend these ones in virtual space. The research questions are: How does the changing from Brazilian religious hegemony to pluralism happen and develop? What are its causes and effects? Is the current religious situation a crisis or a new institutional enhancement? How is cyberspace used by a non-institutional religion? What is God s interface on the Orkut social network? What comprehension can we have about the postings of no religious Internet users on Orkut? The main hypothesis shows that people with no religious belief are a heterogeneous group but not necessarily marked by disbelief, these ones can be classified as: No religion syncretic people, people who move from one church to another, skeptic people about the institution, the agnostics and the atheists. The cyberspace enables a social, cultural and religious reconfiguration of the same ones with a religious breaking within the traditional and no institutional religious system, but the religiosity is still maintained. The first part of thesis analyses the Brazilian religious changes that led to the emerging of people who have no religious belief, that is, the transition of the religious hegemony to the pluralism. Religious changes were worked, which led from the catholic supremacy to the religious pluralism until the emerging of people who have no religious belief in the postmodernity situation process. The second of thesis research part studies people who have no religious belief in the virtual communities, as Orkut in a special way, to understand the action of this social network